Self-Actualization of a Young Teacher’s Personality in Multicultural Educational Environment - Almira M.Garifullina; Venera Zakirova; Svetlana Bashinova; Nadezhda Pomortseva; Aisylu Garifullina (ARPHA Proceedings, 2019)
The process of self-actualization of a teacher within a multicultural educational context creates the foundation for effective cross-cultural communication, tolerance, the development of professional multicultural competencies as well as fosters respect for ethnic minorities. This article demonstrates the importance of teacher self-actualization through the prism of scientific propositions. The latter implies the construction of a new theoretical framework, in which the teacher’s personality is viewed as a "new" set of characteristics, personality traits and abilities necessary for the performance of professional activities. The materials provided in the article might be of interest for pre-school educators, child psychologists, university lecturers as well as for wider audiences. The problem of the study lies in the fact that beginning teachers often fail to realize the full potential of their professional activities, thus raising the questions: what are the common features of a beginning teacher’s personality self-actualization and who contributes to the improvement of quality of the educational process?